Ancient manuscript data security system on national library of Indonesia's Khastara Website - Ayu Kristiani; Elizabeth Sri Lestari; Rudi Latuperissa (Jurnal Mantik, 2023)
This study aims to evaluate the data security system of ancient manuscripts that have been uploaded to the KHASTARA (Khasanah Nusantara) website at the National Library of the Republic of Indonesia. The research method used is a qualitative method with a descriptive approach. The data in this study was collected by conducting an interview with one of the informants engaged in digitizing ancient manuscripts, data and information centers. In addition, data is collected by observing and documenting so that the data obtained is more accurate. The results of this study show that the National Library of Indonesia has preserved ancient manuscripts very well and disseminated the information through the KARTHA website. However, PERPUSNAS RI has not implemented a data security system for its collection of digital ancient manuscripts, only securing its network (firewall). The conclusion of this study is to hope that there will be awareness of all employees on digital ancient manuscript data and the existence of competent human resources in the field of data security.